Advancement of grape maturity: comparison between contrasting cultivars and regions. (17th December 2019) - Cameron, W.; Petrie, P.R.; Barlow, E.W.R.; Patrick, C.J.; Howell, K.; Fuentes, S.
Abstract: Background and Aims: As grapegrowers move to adapt to climate change, they need more detailed information on what cultivars to plant and where to plant them. The aims of this study were to understand how different cultivars in different regions are responding to changes in climate, in order to inform future cultivar selections. Methods and Results: Trends in the day of year maturity (DOYM) between 1999 and 2018 were analysed for 23 grape cultivars (covering at least 7 years) and four Victorian vineyard regions against vintage year, seasonal growing degree day (GDDSep–Mar ) and Spring Index. In most cases there were significant trends in DOYM advancement as a function of GDDSep–Mar and spring index. Temporal advancement of DOYM was more variable. One cultivar showed a significant advancement at two of three sites and another showed a significant delay. Different cultivars advanced DOYM at significantly different rates at a given site, later ripening cultivars advanced DOYM faster than earlier ripening cultivars and for a cultivar grown across several sites, the DOYM advancement was faster at cooler sites. Conclusions: Grapevine cultivars respond to warming temperature differently and the advancement of grape maturity is predicted to slow as temperature further increases. Significance of the Study: The study showed diversity in the phenological response of cultivars to temperature, which may be utilised to better adapt to climate change.